PERCERAIAN WARGA GKJW DI KABUPATEN JEMBER - Imanuel Teguh Harisantoso (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2019)
The congregation of Gereja Kristen Jawi Wetan (GKJW) in Jember is the research subject, and an integral part of that divorce rate is rising. The teaching of the Christian faith is not to be divorced, but divorce occurs. In the 1970s, there were no divorces; however, in the 2000s, divorce befell the GKJW Christian family in Jember. The high divorce of church members in Jember in the 2000s became a challenge to Church service. The data from Jember Regency Population and Civil Registration Office aligns with the divorce in GKJW Congregations in Jember. What factors cause divorce in the GKJW Church in all of Jember District? Social supports, administrative requirements, and religious background are the main factors driving divorce. While supporting factors, husband and wife accountability, PIL or WIL, family conflicts, and communication are the stimulants of divorce. These social facts are intertwined in church service in a societal context. Institutionally or personally, church servants should prepare themselves and the “tools” of the services needed to prepare for possible problems.